Multi-environment PDF modeling for non-catalytic partial oxidation process under MILD oxy-combustion condition. (15th March 2018) - Jeon, Sangtae; Kwon, Minjun; Kim, Yongmo
Abstract: The multi-environment probability density function approach has been applied to numerically investigate the Moderate or Intense Low-Oxygen (MILD) oxy-combustion processes encountered in the non-catalytic partial oxidation (POX) gasifier. The multi-environment PDF approach has the form of a conventional Eulerian scheme and retains the desirable property of a particle-based method. Micro-mixing is represented via the IEM model, and the detailed chemistry is based on GRI 3.0 mechanism without NO x chemistry. In terms of the mean temperature, the present multi-environment PDF approach yields the overall agreement with the measurements in the highly fuel-rich MILD oxy-combustion situation with the strong flue gas recirculation even if there exist the certain discrepancies in the upstream region. Special emphasis is given to the effects of the fuel/oxygen injection velocity and O2 /CH4 ratio on the characteristics of the strongly recirculated MILD oxy-combustion processes. Depending on injection velocity or O2 /CH4 ratio, the present MEPDF approach well reproduces the qualitative flame transition characteristics from MILD combustion to conventional combustion. The higher fuel/oxygen injection velocity leads to the much longer jet penetration and the much higher SDR level which makes the ignition to occur at further downstream region. The relatively lower O2 /CH4 ratios maintain the basic characteristics of the MILD combustion while the highest O2 /CH4 ratio locally creates the oxy-flame like structure rather than the non-visible flame field. Based on numerical results, the detailed discussions are made for flame stabilization, auto-ignition process and precise flame structure in terms of recirculation rate, distribution of turbulent Damköhler number, scalar dissipation rate, mean temperature and mole fraction of CH2 O and OH. Highlights: Multi-environment PDF modeling for fuel-rich MILD oxy-combustion processes. Overall agreement with measured temperature profiles in POX gasifier. Effects of the fuel/oxygen injection velocity and O2/CH4 ratio on POXcharacteristics. Flame stabilization, auto-ignition process, flame structureand reforming process.